Research on Molecular Imprinting Technology and MIP-Based Sensors in Food Safety Detection - Liu, Kun (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the increasing awareness of healthcare, research on food safety has become a focus of researchers. Pesticide residues, veterinary drug residues, heavy metals, and food additives in the food caught the attention of researchers. Therefore, achieving accurate and rapid detection of target objects in food is of great significance for maintaining physical health of human beings. Detecting these target objects based on sensors is an effective way for people to ensure food safety. However, the detection matrix is relatively complex and the concentration of the target substance is extremely low, which bring difficulties for the detection. Therefore, new functional materials with specific identification are selected for sensor modification. Molecular imprinting technique (MIT) has a unique advantage including high selectivity and good stability. This technology can be used to prepare molecularly imprinted polymers (MIPs) which exhibit specific identification. Therefore, using MIP-based sensors for detecting target substances in food can improve detection accuracy. This work focuses on the discussion of MIT and MIP-based sensors. Meanwhile, this work summarizes the application of MIP-based sensors in food safety.